Frozen kuih-muih’s specific sensory attributes, customers’ satisfaction and behavioral intentions / Emi Rozaida Kasbolah - Kasbolah, Emi Rozaida (2013)
The advancement of technology has contributed to the rapid growth and expansion of frozen industry. From raw ingredients such as frozen meat and poultry, it is expanded towards frozen processed foods such as burger patties, ready-meal and snacks. In Malaysia, frozen kuih-muih is one of the sub-sectors of frozen food industry which receives attention from many food manufacturers. Variety kind of frozen kuih-muih can be found in supermarket freezers. People now can enjoy preparing kuih-muih at home by pre-heating the frozen kuih-muih through microwaving, frying, or steaming. Despite of the great expansion of frozen food industry in Malaysia, however the level of customers’ satisfaction towards frozen food products is unknown. Owing to the fact that quality of frozen foods may change due to freezing and frozen storage, and low consumption number of frozen kuih-muih, therefore this study aims to investigate the reaction of customer towards sensory satisfaction of frozen kuih-muih explicitly. Within this context, the relationship between specific sensory attributes, overall satisfaction and behavioral intentions were also examined. Based on extensive literature reviews of food-related attitude and behavior, a study framework was developed. Questionnaires were distributed to 400 respondents in Shah Alam and 71.5% response rate was obtained. Series of statistical analysis comprised of correlation analysis, and multiple regressions analysis were carried out to analyze the data. The results indicate that specific sensory attributes which comprises of appearance, flavor, texture and odor has a significant positive effect on overall satisfaction and behavioral intentions. Improving customer satisfaction on specific sensory attributes, which result in increased overall satisfaction, will further lead to high favorable behavioral intentions such as high rate of re-purchase intentions, strengthen the customer loyalty, spread positive word of mouth, and recommendations. These benefits will in turn improve business reputation, portray good business image and generate greater revenue.